Responsabilidad familiar en el desarrollo integral de niños y niñas de los centros de educación inicial de toctiuco, propuesta de un sistema de capacitación integral para padres de familia. - Calvopiña Molina, Mélida Luzmila (2014)
The infant stage submits own characteristics that are related to the development of children since the ages 3 to5 years. It constitutes the basis for the physical and spiritual development, where are they assimilated knowledge, skills, abilities; also they are formed capacities, volitional-moral qualitieswhat in the past was considered possible only in children of older ages. The current research likes to show the transcendence of a good treatment and attention to the children in their first years of life, since this attention will depend the adult type what will be had in the future. The preschool Centers attend and stimulate the children development, while are found under their responsibility, but the hours that children spend in the Centers, they doesn’t equivalent to less than 25%. Most of the time, they spend under the care of their parents; hence, the current research importance knowing what is the attention degree that received at home and the quality of it. The hypotheses that guide the research work are referred what the parents fromEduardo Villaquirán Initial Education Center disown how to attend their children and how to encourage their development and identify the interest, thereof, for knowing infant stimulation training, to upgrade the children capacities and create an emotional and pleasant environment. The research results can test the hypotheses, thereby, justify one of the aims from work refers to the necessity of making a training guide on the child development by parent, it is not enough appropriate carethe child gets in the school centers, the same stress should prolong at home to really talk about happy and well attended children. The research beneficiaries will be the children, parents, teachers, of directand general manner.